Benin-Urhobo Relations Under Colonial Rule: Genesis of Conflicts over Land Resources and Use - Opone, Paul O. (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025DO - 10.58709/niujss.v11i4.2325, 2025)
This study focuses on Benin-Urhobo relations under colonial rule. Both groups have had long periods of contact with mutual benefits. However, British colonial rule adversely altered that cordial relationship and incorporated them into the world market over which they had no control. This paper aims to show how the Binis and Urhobos responded to the opportunities and crises generated by internal development challenges and by external political and economic forces, stimulated by British colonial rule in the general area. The paper depended on primary and secondary sources. It deploys the historical method of descriptive analysis to address the subject. The findings indicate that the struggle over access to and control of forest and water resources, and their use, engendered conflict in Benin-Urhobo relations during the colonial dispensation and was followed by steps taken by the colonial government to reduce the power and influence of the Benin Oba over the Urhobo group. Underneath this was the British determination to ensure free trade between the Urhobo and the European trading firms. It concludes that the struggle over land resources occasioned by the colonial policy had far-reaching implications on their relationship under colonial rule and beyond.         Keywords: Benin-Urhobo, Inter-Group Relations; Colonial Dispensation, Resources Use, Free Trade, The Genesis of Crisis.